Three-Dimensional Isotropic MRI of the Cervical Spine: A Diagnostic Comparison With Conventional MRI. Issue 2 (March 2016) - Fu, Michael C.; Buerba, Rafael A.; Neway, William E.; Brown, James E.; Trivedi, Mitesh; Lischuk, Andrew W.; Haims, Andrew H.; Grauer, Jonathan N.
Abstract : Study Design: Retrospective diagnostic trial. Objective: To determine the diagnostic performance of 3-dimensional turbo spin-echo (3D-TSE) isotropic magnetic resonance imaging (MRI) in the assessment of cervical spine pathology. Summary of Background Data: MRI is the imaging modality of choice for many cervical spine pathologies. However, axial imaging may be suboptimal if the image plane is oriented differently than the plane of interest, due to lordosis, kyphosis, or deformity. 3D-TSE isotropic MRI is a promising novel technology that bypasses this limitation by enabling dynamic image reformation in any desired orientation. Methods: Forty-eight patients who underwent 3D-TSE and conventional 2-dimensional fast spin-echo (2D-FSE) T2-weighted cervical spine MRI at our institution were randomly selected. 3D-TSE and 2D-FSE sequences from each subject were independently evaluated by 2 orthopedic spine surgeons and 4 musculoskeletal radiologists. Images were assessed using specific pilot-tested criteria for stenosis, herniation, and degenerative changes. Intermethod, interrater, and intrarater agreements for 3D-TSE and 2D-FSE, and Fleiss κ coefficients were determined. Results: The overall intermethod agreement was 80.7%. The interrater agreement was 75.9% for 3D-TSE and 75.7% for 2D-FSE ( P =0.47). The intrarater agreement was 82.2% for 3D-TSE and 81.5% for 2D-FSE ( P =0.71). Fleiss κ coefficients were 0.42 for 3D-TSE and 0.43 for 2D-FSE ( P =0.62), indicating moderate interrater reliability. The intermethod agreement and the 2D-FSE intrarater agreement were statistically similar ( P =0.49). Conclusions: There is a high degree of agreement between 3D-TSE and 2D-FSE MRI in assessing the cervical spine. The intermethod variability was statistically similar to the intrinsic intrarater variability of 2D-FSE MRI. This study demonstrates that 3D-TSE yields at least equivalent diagnostic information as conventional 2D-FSE in the cervical spine. In addition, reviewers noted subjective advantages of 3D-TSE image reprocessing, especially when evaluating greater pathology or deformity, with a simplified image acquisition process.